Factors associated with esophageal stricture formation after endoscopic mucosal resection for neoplastic Barrett’s esophagus - Lewis, Jason J. (2011)
BACKGROUND: EMR for early neoplastic Barrett’s esophagus is gaining favor over esophagectomy. Esophageal stricture development has been reported as a common complication of EMR, photodynamic therapy, and combination endoscopic therapy. OBJECTIVE: To determine clinical and procedural predictors of symptomatic stricture formation after EMR. DESIGN: Retrospective analysis. SETTING: Tertiary-care referral university hospital. PATIENTS: Data were retrospectively reviewed on 73 patients at our institution who underwent EMR monotherapy for Barrett’s esophagus with high-grade dysplasia or intramucosal cancer since January 2006. INTERVENTION: EMR. MAIN OUTCOME MEASUREMENTS: Symptomatic esophageal stricture formation. RESULTS: Symptomatic esophageal stricture formation was noted in 24.7% of patients undergoing EMR. Stricture formation on univariate analysis was associated with percentage of circumference of esophageal lumen resected, total pieces resected, number of EMR sessions, and tobacco use. A threshold effect was found at 50% of esophageal circumference resected (66.7% vs 27.2% developed strictures above and below the threshold, respectively; P = .004). A 25-pack-year or greater history of tobacco use had a threshold effect on esophageal stricture formation (77.8% vs 7.2% developed strictures above and below the threshold, respectively; P =.02). In multivariate analysis, resection of >50% of the circumference was strongly associated with stricture formation (odds ratio [OR] 4.17; 95% confidence interval [CI], 1.27–13.7). A 25-pack-year or greater history of tobacco use also trended toward stricture formation (OR 3.33; 95% CI, 0.929–12.1). LIMITATIONS: Retrospective design, sample size. CONCLUSION: Resection of at least 50% of the esophageal mucosal circumference is strongly associated with stricture formation. Patients with strong histories of tobacco use also may be more likely to develop esophageal strictures following EMR.